MP010: Wraparound care for youth injured by violence: a randomized control trial. (2nd June 2016) - Snider, C.; Chernomas, W.; Cook, K.; Jiang, D.; Klassen, T.; Logsetty, S.; Mahmood, J.; Mordoch, E.; Strome, T.
Abstract : Introduction: Youth injured by violence is a major public health concern in Canada. It is the fourth leading cause of death in youth and the foremost reason youth visit an emergency department (ED). In Winnipeg, 20% of youth who visit an ED with an injury due to violence will have an ED visit for a subsequent violent injury within one year. Youth injured by violence are in a reflective and receptive state of mind, rendering the ED setting appropriate for intervention.Methods: We completed a randomized control trial in November 2015 comparing wraparound care for youth age 14 - 24 who were injured by violence to standard ED care. Youth were excluded if their injury was due to child maltreatment, sexual assault or self-harm. An adapted pre-consent randomization methodology was used. The intervention was developed using a community based participatory research approach. Wraparound care was delivered by a support worker with lived experience with violence. Support workers were on call 24/7 in order to start the intervention in the ED and take advantage of the "teachable moment." Care continued in the community for approximately one year.Results: A total of 133 youth were randomized (68 intervention, 65 control) in one year. There was no difference in age, gender, or severity of injury between the two groups. Patients randomized to the intervention spent a median of 30 minutes less in the ED than those receiving standard care (p=0.22). Youth are safely housed, have enrolled in education opportunities, and are engaged in addictions care. Results of a chart review examining repeat visits to the ED for violent injury, substance use and mental health will be completed in Spring 2016 and will be presented.Conclusion: There were no differences between standard care and intervention groups on baseline characteristics reflecting effective randomization. The introduction of an intervention at bedside in the ED did not have a negative impact on patient length of stay.